Differential Effect of Calsequestrin Ablation on Structure and Function of Fast and Slow Skeletal Muscle Fibers - Paolini, Cecilia (Hindawi Publishing Corporation, 2011)
We compared structure and function of EDL and Soleus muscles in adult (4–6 m) mice lacking both Calsequestrin (CASQ) isoforms, the main SR Ca(2+)-binding proteins. Lack of CASQ induced ultrastructural alterations in ~30% of Soleus fibers, but not in EDL. Twitch time parameters were prolonged in both muscles, although tension was not reduced. However, when stimulated for 2 sec at 100 hz, Soleus was able to sustain contraction, while in EDL active tension declined by 70–80%. The results presented in this paper unmask a differential effect of CASQ1&2 ablation in fast versus slow fibers. CASQ is essential in EDL to provide large amount of Ca(2+) released from the SR during tetanic stimulation. In contrast, Soleus deals much better with lack of CASQ because slow fibers require lower Ca(2+) amounts and slower cycling to function properly. Nevertheless, Soleus suffers more severe structural damage, possibly because SR Ca(2+) leak is more pronounced.